Recovery of centralities in medial prefrontal and sensory-related cortices associated with social behavior improvements in an autism mouse model - Hiroki Ueno; Yusuke Iyanaga; Katsuyuki Kunida; Yuta Hara; Hiroki Miura; Yuka Nakai; Masato Tanuma; Misuzu Hayashida; Rei Yokoyama; Jin Ohkubo; Kaoru Seiriki; Atsuko Hayata-Takano; et al. (Scientific Reports)
Abstract Anti-epileptics and diuretics, used for unapproved purposes, have been reported to ameliorate social deficits in individuals with autism spectrum disorder. However, the underlying neural mechanisms remain unclear. Here, we explored the effects of bumetanide, clonazepam, and phenytoin, all with clinically reported properties for improving social deficits, in a prenatal valproic acid exposure male mouse model. By combining comprehensive behavioral analysis with brain-wide mapping of Arc, an immediate early gene, we found a correlation between social behaviors and Arc-positive cell counts across brain areas. Network analysis identified the medial prefrontal and sensory-related cortices as critical nodes with high centrality, playing critical roles in connecting other brain regions. These metrics are associated with both the decreased social behaviors and their recovery following drug treatment. Our findings suggest that restoring the centralities of the medial prefrontal and sensory-related cortices serve as a potential biomarker for evaluating drug efficacy in autism spectrum disorder.